Empowerment of Cadres and Pregnant Women Through Education on The Utilization of Herbal Drinks In Managing Hyperemesis Gravidarum - Winda, Desy; Rahmana, Fatma Richa; Anggraini, Shelly Puspa (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This program aimed to improve the knowledge and skills of cadres and pregnant women in utilizing herbal drinks made from ginger and lemongrass as a non-pharmacological alternative to reduce symptoms of hyperemesis gravidarum. Method: Activities included socialization, education, demonstrations, and hands-on practice, supported by learning media such as leaflets, pocket books, and videos. Evaluation was conducted through pre-test and post-test on 20 participants. Practical Applications: The training is expected to encourage independent application of herbal drinks at home, strengthen cadres’ role in continuous education, and open opportunities for developing herbal products with economic value. Conclusion: The program successfully increased participants’ knowledge from 52.5% to 94.5% and reduced nausea and vomiting complaints after routine consumption. This intervention has the potential to be replicated in other Posyandu to support maternal health and community empowerment.